2019
DOI: 10.3390/en12112185
|View full text |Cite
|
Sign up to set email alerts
|

Emissivity Characteristics of Hydrocarbon Flame and Temperature Measurement by Color Image Processing

Abstract: Non-gray radiation should be considered in the temperature and emissivity measurements of hydrocarbon flames. In this paper an improved ratio pyrometry by spectral analysis and color image processing is proposed. A Newton-type iterative method is utilized to analyze the spectrometer signals for the detection of monochromatic emissivity, and then the ratio pyrometry based on color image processing is corrected by the detected monochromatic emissivity without making approximations of the filter profiles of CCD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The radiative properties of triatomic gases show strong spectral selectivity, and the characteristics of soot particles are closely related to temperature, wavelength and radiation. Radiation thermometry based on colour image processing has proven to be effective in measuring flame temperature and allows cost savings [2]. Colour CCD cameras were used to investigate the simultaneous measurement of temperature distribution and radiative properties by radiation analysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The radiative properties of triatomic gases show strong spectral selectivity, and the characteristics of soot particles are closely related to temperature, wavelength and radiation. Radiation thermometry based on colour image processing has proven to be effective in measuring flame temperature and allows cost savings [2]. Colour CCD cameras were used to investigate the simultaneous measurement of temperature distribution and radiative properties by radiation analysis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 22 used a polynomial function to model the candle flame emissivity; the results showed that the emissivity of the candle flame decreased with an increasing wavelength. Lin et al 23 used a polynomial function to model the emissivity of a hydrocarbon flame; the relative error between the temperature measurements and the thermocouple results was less than 8.34%. Fu et al 24 used a dual bandpass filter to obtain twocolor radiation images at 643 and 564 nm; the temperature of the blackbody furnace was measured on the basis of the gray model.…”
Section: Introductionmentioning
confidence: 99%